American GI Forum 1992 - San Jose Queen Coronation Rehersal (and Other Event) - Castellano, Alcario:::creator:::::::::::: (2024)
Video and transcripts of the rehersal for the 1992 American GI Forum - San Jose chapter Queen Coronation. Also included is a video of a youth baseball game (7:55).